A Review of Lithium-ion Battery Capacity Fade Deceleration at Power Fluctuations in Renewable Energy Systems - Gwayi, Isaac; Ayeng’o, Sarah; Kimambo, Cuthbert (Tanzania Journal of Engineering and Technology, 2025)
Application of lithium-ion (Li-ion) batteries to store energy in renewable energy systems (RESs) is increasing due to their promising properties. Therefore, it is crucial to understand aging behaviours of Li-ion battery during RES life time as this directly affects cost of energy. Li-ion battery aging can be categorised into calendar aging and cycle aging. Calendar aging depends mainly on temperature and state of charge (SoC). In addition to temperature and SoC, cycle aging depends also on charge and discharge current rates and cut-off voltages. Higher current rates lead to faster Li-ion battery aging. It is necessary to identify appropriate battery power control strategies and their configuration to decelerate batteries’ aging in RESs. In this paper, a review of effects of power fluctuations on cycle life of Li-ion batteries in RESs has been done. Furthermore, hybrid energy storage systems (HESS), comprising battery system (BS) and supercapacitor (SC), topologies and control strategies are studied. Literature focussing on BS-SC systems in RESs was reviewed aiming at finding commonly used topologies and strategies. It has been found that the most commonly used methods in BS-SC HESS are classical strategies (70%) and fullactive converter topology (80%). The study recommends using classical control strategies and full-active converter topology during BS-SC implementation in RESs. Furthermore, the study recommends that future research should focus on evaluating in detail technical and economic factors of the identified control strategies and HESS converter configurations